Why Graphics Powers Is Revolutionizing Physics. - Macedonia, Michael (Computer (00189162), 2006)
The article discusses the influence of graphics in revolutionizing physics. Videogames use computer to imitate an abstracted environment and as it become more visual and with the arrival of raster graphics and color, modeling physics has become its component. Physics-based engines encourage the development of commercial libraries in software developer's kit (SDK). SDK offers routines for collision detection, vehicle dynamics, constraint solving and rag-doll physics which allow game characters to fall and get up realistically while taking action in uneven terrain and obstacles. The influence that the graphics processing unit and physics processing unit supplied in representing physics has been applied to various uses beyond the world of games.